2019
DOI: 10.3892/mmr.2019.10483
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of ISO‑1 against advanced glycation end product aggravation of PC12 cell injury induced by Aβ1‑40

Abstract: Advanced glycation end products (AGEs) are important pathogenic substances involved in diabetes mellitus (DM) and its complications. AGEs also serve important roles in promoting the development of Alzheimer's disease (AD). Macrophage migration inhibitory factor (MIF), an inflammatory stimulant and a pathogenic factor involved in DM, was previously reported to be present at increased levels in the cerebrospinal fluid of patients with AD and mild cognitive impairment compared with age-matched healthy controls. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…In another in-vitro study it was shown that the small molecule inhibitor of MIF ISO-1 protected PC12 cells from advanced glycation end product (AGE) aggravation of PC12 cell injury induced by Aβ 1-40 [56]. This finding may indicate that AGE may represent a pathogenetic link between type 2 diabetes and AD, and that MIF may be a common pathogenetic mediator [56].…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…In another in-vitro study it was shown that the small molecule inhibitor of MIF ISO-1 protected PC12 cells from advanced glycation end product (AGE) aggravation of PC12 cell injury induced by Aβ 1-40 [56]. This finding may indicate that AGE may represent a pathogenetic link between type 2 diabetes and AD, and that MIF may be a common pathogenetic mediator [56].…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…This line is easy to handle and homogenous [173], while the cells can undergo neuronal differentiation in response to nerve growth factors resulting in large numbers of post-mitotic cells [174]. Many researchers have worked with this line to study neurodegeneration [175,176] and neurotoxicity caused by AGEs [177][178][179][180]. PC12 cells express RAGE [179] and they were vulnerable to ribosylated-BSA induced cytotoxicity, while the exposure increased iNOS and COX-2 expression and phosphorylation of p38 [178].…”
mentioning
confidence: 99%
“…As an intrinsic by product of ATP production, mitochondria also produce reactive oxygen species (ROS) [ 23 ]. Many previous studies have demonstrated that ROS are important factors in aging.…”
Section: Resultsmentioning
confidence: 99%